In-situ cured silicon-based negative electrode lithium battery and preparation method thereof
By forming a strong bond between the silicon-based negative electrode and the in-situ solid electrolyte, the fluoroalkyl functional groups in the polymer monomer interact with the hydroxyl group on the surface of the silicon-based negative electrode to achieve in-situ curing of the polymer, solving the interface problems of the silicon-based negative electrode in all-solid lithium batteries, and improving the cyclic stability and energy density of the battery.
Patent Information
- Application Number
- CN202411982763.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Silicon-based anode has serious interface problems in all-solid-state lithium batteries, resulting in a decrease in cycle stability and electrochemical performance, limiting its commercial application.
By forming a strong bond between the silicon-based negative electrode and the in-situ solid electrolyte, the fluoroalkyl functional groups in the polymer monomer interact with the hydroxyl groups on the surface of the silicon-based negative electrode to achieve in-situ curing of the polymer, thereby forming a stable and solid negative electrode-solid electrolyte interface.
It effectively suppresses the volume expansion of the silicon-based negative electrode during the circulation process, improves the adhesion between active material particles, improves interface contact, enhances the cycle stability and energy density of the battery, and improves the safety performance of the battery at high temperatures and high voltages.
Smart Images

Figure CN119786715A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to an in-situ solidified silicon-based negative electrode lithium battery and a preparation method thereof. Background Art
[0002] At present, the negative electrode materials of commercial lithium-ion batteries are mainly graphite, etc. High specific energy alloy negative electrode materials (such as Si, Sn, P, etc.) have gradually attracted attention and application due to their high specific capacity. Taking silicon-based negative electrode as an example, Li 3.75 Si has up to 3580mAh g -1 The lithium insertion capacity is higher and the redox potential is lower (0.2-0.4V vs Li + / Li) and lower cost, it is expected to meet the demand for high-energy-density batteries.
[0003] The silicon-based negative electrode faces a dramatic volume change (about 300%) during the alloying / dealloying process. On the one hand, this will lead to the continuous fragmentation and recombination of SEI, which will cause the continuous loss of active lithium and affect the cycle life of the whole battery. On the other hand, the continuous stress will also cause particle pulverization and binder failure, making the silicon negative electrode face more serious cycle problems. Nano-sizing silicon can alleviate the above-mentioned problems caused by its volume expansion, but it will lead to increased costs and reduced compaction density, which limits the commercial application of silicon-based negative electrodes. In the existing technology, carbon materials / LiSiO are introduced into the silicon negative electrode. x Spatially confined materials are an effective way to mitigate volume expansion. However, the fundamental issue of dynamic interface evolution between silicon-based materials and the electrolyte in liquid lithium-ion batteries as anodes is that they are subject to significant challenges. Overall, the application of high-silicon / pure silicon anodes in liquid lithium-ion batteries faces significant obstacles.
[0004] In contrast, due to the mechanical hardness and external stacking pressure of inorganic solid electrolytes, the silicon negative electrode in solid-state batteries will exhibit a different SEI generation and evolution mechanism from that in liquid lithium-ion batteries, thus providing an opportunity to achieve better cycle stability. Yi ng Shi rl ey Meng et al. used 99.9wt% micron silicon combined with a sulfide solid electrolyte (Li6PS5Cl) to obtain an all-solid-state battery with high current density and high areal loading. The successful application of micron silicon came from the two-dimensional interface passivation of the sulfide solid electrolyte-silicon, which limited the continuous growth of SE I. However, all-solid-state batteries with silicon negative electrodes require an external stacking pressure of 50-150MPa to maintain interfacial contact between silicon / silicon and silicon / electrolyte. Although increasing the pressure can improve the performance of solid-state batteries to a certain extent, excessively high stacking pressure faces difficulties in practical applications. Furthermore, although many studies have reported the excellent performance of sulfide solid electrolytes paired with silicon anodes, experimental batteries typically use thicker sulfide electrolyte membranes, such as those exceeding 1 mm. Using thinner sulfide electrolyte membranes can lead to potential problems such as membrane formation difficulties and dendrite penetration, resulting in the inability to achieve high-energy-density batteries in practical applications of silicon anodes. Therefore, the practical industrialization of all-solid-state batteries with silicon anodes paired with sulfide solid electrolytes still faces many challenges.
[0005] In summary, silicon-based anodes, when used in all-solid-state batteries, still face serious interface issues with the solid electrolyte. Existing solutions are unable to effectively address these issues and inevitably lead to a decline in the electrochemical and mechanical performance of solid-state batteries. Therefore, there is an urgent need to improve solid-state lithium batteries with silicon-based anodes to address these challenges in practical use. Summary of the Invention
[0006] The purpose of the present invention is to address the defects of the prior art and provide an in-situ solidified silicon-based negative electrode lithium battery and a preparation method thereof. The present invention utilizes the interaction between the fluoroalkyl functional groups of the polymerized monomers in the precursor solution and the -OH functional groups enriched on the surface of the silicon-based negative electrode material to form a strong bond between the silicon-based negative electrode and the in-situ solid electrolyte. This can not only effectively suppress the volume expansion of the silicon negative electrode during the cycle, increase the adhesion between the active material particles, improve the interface contact problem between the silicon-based negative electrode and the polymer electrolyte, effectively ensure the contact and transmission of ions and electrons, but also protect the surface of the silicon-based negative electrode, thereby improving the cycle stability of the battery system at high temperature and high voltage, and improving the energy density and safety performance of the battery.
[0007] To achieve the above objectives, in a first aspect, the present invention provides an in-situ solidified silicon-based negative electrode lithium battery, comprising: a positive electrode, a silicon-based negative electrode, and an in-situ solid electrolyte between the positive electrode and the silicon-based negative electrode, wherein the in-situ solid electrolyte is obtained by in-situ polymerization of a polymer precursor solution;
[0008] The polymer precursor solution includes a polymer monomer containing a fluoroalkyl group; the surface of the material of the silicon-based negative electrode is rich in hydroxyl groups;
[0009] The silicon-based negative electrode and the in-situ solid electrolyte form a stable bond through at least two of hydrogen bonding, dipole-dipole interaction, free radical polymerization and van der Waals force;
[0010] The fluorine concentration in the in-situ solid electrolyte is distributed in a gradient, gradually decreasing from the silicon-based negative electrode side to the positive electrode side.
[0011] Preferably, the polymerizable monomer is a composite system comprising: carbonate, acrylate and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3), preferably vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) in a volume ratio of (1-3):1:(1-3).
[0012] Preferably, the polymer precursor solution further comprises lithium salt, and the mass ratio of the polymerizable monomer to the lithium salt is 1:2-2:1; and / or,
[0013] The polymer precursor solution further includes an initiator, and the mass percentage of the initiator in the polymer precursor solution is 0.05%-1%.
[0014] Preferably, the material of the silicon-based negative electrode is a silicon-based material or a composite material of silicon and carbon;
[0015] The silicon-based material includes: one or more of pure silicon, silicon-carbon compounds, lithium-silicon compounds, lithium-silicon-carbon compounds, and silicon-oxygen compound materials;
[0016] The composite material of silicon and carbon is preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:10.
[0017] Preferably, an intermediate membrane is further included between the positive electrode and the silicon-based negative electrode, and the intermediate membrane is used as a supporting material for the in-situ solid electrolyte and as an isolation between the positive electrode and the silicon-based negative electrode.
[0018] Preferably, the silicon-based negative electrode lithium battery further includes an inorganic solid electrolyte; the inorganic solid electrolyte includes: one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
[0019] In a second aspect, an embodiment of the present invention provides a method for preparing an in-situ cured silicon-based negative electrode lithium battery as described in the first aspect, comprising:
[0020] Prepare the positive electrode and the silicon-based negative electrode;
[0021] preparing a polymer precursor solution;
[0022] Assembling a battery with the positive electrode and the silicon-based negative electrode, and injecting the polymer precursor solution into the battery; the injection amount of the precursor solution is 1-10g / Ah;
[0023] The polymer precursor solution is polymerized by initiating light and / or heat to obtain the in-situ cured silicon-based negative electrode lithium battery.
[0024] Preferably, the preparation of the polymer precursor solution specifically includes:
[0025] Mixing carbonate, acrylate, and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3), preferably mixing vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA), and perfluorooctyl ethyl acrylate (PFOEMA) in a volume ratio of (1-3):1:(1-3) to obtain a polymerized monomer;
[0026] The polymerizable monomer is added to a clarified solution containing lithium salt in a mass ratio of 1:2 to 2:1, and after mixing evenly, an initiator is added in an amount of 0.05% to 1% by mass of the entire polymer precursor solution, and the mixture is mixed evenly to obtain a polymer precursor solution;
[0027] The clear solution containing lithium salt comprises: lithium salt and a solvent capable of dissociating the lithium salt; the solvent comprises one or more of a liquid organic solvent capable of dissolving the lithium salt and a solid organic matter capable of forming a homogeneous solution after being mixed with the lithium salt; and the lithium salt concentration of the solution is 0.1-10 mol / L.
[0028] Preferably, the material of the silicon-based negative electrode is a silicon-based material or a composite material of silicon and carbon;
[0029] The silicon-based material includes: one or more of pure silicon, silicon-carbon compounds, lithium-silicon compounds, lithium-silicon-carbon compounds, and silicon-oxygen compound materials;
[0030] The composite material of silicon and carbon is preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:10.
[0031] Preferably, when assembling a battery using the positive electrode and the silicon-based negative electrode, an intermediate membrane is further installed between the positive electrode and the silicon-based negative electrode, and the intermediate membrane is used as a supporting material for the in-situ solid electrolyte and as an isolation between the positive electrode and the silicon-based negative electrode.
[0032] The in-situ solidified silicon-based negative electrode lithium battery provided by the embodiment of the present invention includes a positive electrode, a silicon-based negative electrode, and an in-situ solid electrolyte between the positive electrode and the silicon-based negative electrode. The surface of the silicon-based negative electrode is rich in a large number of hydroxyl groups. The in-situ solid electrolyte is obtained by in-situ polymerization of a polymer precursor solution. The polymerization monomer in the polymer precursor solution contains a fluoroalkyl functional group. The fluoroalkyl group has a strong interaction with the hydroxyl group on the surface of the silicon-based negative electrode, thereby achieving the aggregation of fluorine-containing polymers on the surface of the silicon-based negative electrode particles, and the polymer and the silicon-based negative electrode form a strong bond due to molecular forces, so that a stable and strong bond is formed between the in-situ solid electrolyte and the silicon-based negative electrode after in-situ polymerization. This stable and firmly bonded negative electrode-solid electrolyte interface can not only effectively suppress the volume expansion of the silicon-based negative electrode during the electrochemical cycle, but also effectively improve the interface performance and fully ensure the contact and transmission between ions. This stable anode-solid electrolyte interface not only effectively inhibits corrosion of the silicon-based anode by additives with low reduction stability or residual precursor monomers, but also more effectively matches the high-voltage positive electrode, thereby fully ensuring the high energy density and long-cycle stability of the lithium battery system. In addition, the fluoroalkyl group in the polymer monomer can significantly improve the thermal stability of the polymer electrolyte, thereby effectively ensuring the cycle stability of silicon-based anode batteries at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscopy (SEM) image of a cross section of the material obtained after polymerization of the precursor solution in Example 1 of the present invention;
[0034] Figure 2 This is a SEM image of the surface of the material obtained after polymerization of the precursor solution in Example 1 of the present invention;
[0035] Figure 3 FTIR analysis of the material before and after polymerization of the monomers in the precursor solution of Example 1 of the present invention;
[0036] Figure 4 This is a graph showing the 0.5C cycle performance test at 30°C for button batteries assembled from Examples 1-5 of the present invention and Comparative Examples 1-4;
[0037] Figure 5 This is a test chart of the high-temperature charge and discharge performance of button batteries assembled in Example 1 of the present invention and Comparative Example 1 at 60°C;
[0038] Figure 6This is a test diagram of the charge and discharge performance of the full battery assembled in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0040] An embodiment of the present invention provides an in-situ solidified silicon-based negative electrode lithium battery, comprising: a positive electrode, a silicon-based negative electrode, and an in-situ solid electrolyte between the positive electrode and the silicon-based negative electrode.
[0041] The positive electrode in the lithium battery of the present invention can include any positive electrode material, for example, including lithium iron phosphate, lithium cobalt oxide, ternary materials, or lithium-rich manganese-based positive electrode materials. The in-situ cured silicon-based negative electrode lithium battery of the present invention can be compatible with a variety of positive electrodes, including high-voltage positive electrodes and high-capacity positive electrodes, thereby achieving a high-energy density battery suitable for the application.
[0042] The negative electrode of the lithium battery of the present invention comprises a silicon-based material or a silicon-based composite material. The silicon-based material includes one or more of pure silicon, silicon-carbon compounds, lithium-silicon compounds, lithium-silicon-carbon compounds, and silicon-oxygen compounds; the lithium-silicon compound includes a lithium-silicon alloy or a compound formed by carbon and silicon in any proportion, including but not limited to Li 3.75 Si, Li3Si, Li2Si and Li4Si; lithium silicon carbon compounds include lithium silicon carbon alloys or compounds formed by lithium, carbon and silicon in any proportion; silicon oxide compounds include silicon and silicon dioxide composite silicon oxide (SiO x ), but not limited to the above materials. Silicon-based composite materials can include composite materials of silicon and carbon. Silicon and carbon can be mixed together to form a composite material. A composite material can also be formed by coating the surface of a silicon material with carbon. A silicon material can also be loaded on a carbon-based material. Nano-silicon (nano-silicon carbon) can also be deposited in the pores of a carbon medium. The silicon and carbon mentioned above can be nanoparticles or tubular materials, such as carbon nanotubes. The composite material of silicon and carbon is preferably a composite material of silicon and graphite. The mass ratio of graphite to silicon in the composite material is 0:100-90:10, that is, the mass percentage of graphite is 0-90%, for example, 0, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, but is not limited to the above values.
[0043] The surface of the material of the silicon-based negative electrode of the present invention is rich in hydroxyl groups, which is related to the chemical properties of silicon and the surface treatment process in the preparation of its silicon-based materials. First, silicon materials easily form a surface oxide film in the air, that is, a silicon dioxide (SiO2) film, and silicon dioxide undergoes a hydrolysis reaction in water or a humid environment to generate surface hydroxyl groups (-OH). Secondly, in the existing preparation process, in order to enhance the compatibility of silicon-based materials with electrolytes, the silicon surface is usually activated, such as oxidizing acid treatment (for example, hydrogen peroxide and concentrated sulfuric acid are mixed in a volume ratio of 30:70 and boiled at 70°C for 30 minutes to 1 hour), alkaline washing or plasma treatment. These processes will further increase the hydroxyl content on the silicon surface. Silicon-based negative electrode materials rich in hydroxyl groups can form stronger interfacial bonds with polymerized monomers or other functional groups in the electrolyte through hydrogen bonds or chemical bonds. The inventors made full use of the surface properties of silicon-based negative electrode materials and selected polymer monomers containing specific functional groups (such as fluoroalkyl groups). Through the strong interaction formed between the two, not only the binding force between the silicon-based negative electrode and the in-situ polymer electrolyte was greatly improved, but also the distribution and formation of the in-situ polymer electrolyte in the lithium battery was changed.
[0044] The in-situ solid-state electrolyte of the present invention is obtained through an in-situ polymerization reaction of a polymer precursor solution. The polymerizable monomers of the present invention are a composite system comprising: a carbonate, an acrylate, and a fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3). In a preferred embodiment, the composite system utilizes a composite solution of vinylene carbonate, ethylene glycol dimethacrylate, and perfluorooctyl ethyl acrylate in the aforementioned volume ratio as the polymerizable monomers. This composite system ensures that the polymer electrolyte system exhibits excellent ionic conductivity and mechanical properties. Among them, the role of carbonates such as vinylene carbonate is to dissociate lithium salts, thereby ensuring the effective conduction of lithium ions. Ethylene glycol dimethacrylate as a cross-linking agent in the system can improve the mechanical properties of the polymer electrolyte. Fluoroalkyl acrylates such as perfluorooctyl ethyl acrylate can be highly enriched on the silicon surface, that is, through the interaction between fluoroalkyl and hydroxyl groups, perfluorooctyl ethyl acrylate is enriched on the surface of silicon to form a local concentration. As a result, perfluorooctyl ethyl acrylate polymers form a certain gradient distribution in the polymer electrolyte system, wherein the concentration of perfluorooctyl ethyl acrylate polymers on the surface of the silicon negative electrode is relatively high, and the concentration of polyperfluorooctyl ethyl acrylate in the electrolyte is relatively low, thereby forming an interface with excellent mechanical properties and rich fluorine on the negative electrode side, thereby ensuring mechanical stability and electrochemical stability during subsequent electrochemical cycles.
[0045] Furthermore, the polymer precursor solution also includes lithium salt, and the mass ratio of the polymer monomer to the lithium salt is 1:2-2:1.
[0046] Furthermore, the polymer precursor solution also includes an initiator, a substance that initiates polymerization of the monomers, including but not limited to free radical initiators such as azobisisobutyronitrile (AIBN) and 2-hydroxy-2-methyl-1-phenylpropanone. The mass percentage of the initiator in the polymer precursor solution is 0.05%-1%. The mass percentage can be any value within the above range, such as 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, or 1.0%.
[0047] The polymerization monomer in the polymer precursor solution contains fluoroalkyl groups, which have a strong interaction with the hydroxyl groups on the silicon surface. The formed fluoroalkyl polymer is enriched on the surface of the silicon-based negative electrode, and the concentration of the fluoroalkyl polymer gradually decreases from the negative electrode to the diaphragm, thereby forming a gradient distribution. As a result, an interface with excellent mechanical properties and rich fluorine is formed on the negative electrode side, ensuring mechanical stability and electrochemical stability during subsequent electrochemical cycles.
[0048] The strong interaction between fluoroalkyl groups and hydroxyl groups on the silicon surface is because the surface of silicon-based negative electrode materials is rich in hydroxyl groups (-OH), which can form strong hydrogen bonds with fluorine atoms in fluoroalkyl monomers. The high electronegativity of fluorine atoms enables them to form strong intermolecular forces with hydrogen atoms in hydroxyl groups. In addition, the polar groups in fluoroalkyl monomers may undergo electrostatic attraction with local polar regions on the surface of silicon-based negative electrodes, further promoting the adsorption and enrichment of fluoroalkyl monomers. These strong interactions cause fluoroalkyl monomers to preferentially aggregate on the surface of silicon-based negative electrodes and form a layer of fluorine-rich polymers in subsequent polymerization reactions.
[0049] The formation of the gradient distribution is mainly due to the fact that during the preparation process of the in-situ solidified silicon-based negative electrode lithium battery (the preparation method will be described later), after the polymer precursor solution is injected, the fluoroalkyl-containing polymer monomer is rapidly enriched on the surface of the silicon-based negative electrode due to the strong interaction mentioned above. In the area away from the negative electrode surface (such as near the diaphragm), this interaction is weakened, causing the concentration of the fluoroalkyl monomer to gradually decrease along this direction. In addition, since the concentration of the fluoroalkyl monomer enriched on the silicon-based surface is higher, the polymerization reaction rate is also faster, and a fluorine-rich polymer layer is preferentially formed on the negative electrode surface; while in the area away from the negative electrode, the monomer concentration is lower and the polymerization reaction is slower, resulting in a gradient distribution.
[0050] The silicon-based negative electrode of the present invention and the in-situ solid electrolyte form a stable bond through at least two of hydrogen bonding, dipole-dipole interaction, free radical polymerization and van der Waals force. In addition to the hydrogen bonding described above, the fluoroalkyl group has a strong dipole moment, and the hydroxyl group on the surface of the silicon-based negative electrode also has a dipole characteristic. This dipole-dipole interaction can further stabilize the aggregation of the fluoroalkyl monomer on the silicon-based surface. In addition, the fluoroalkyl monomer and the hydroxyl group on the surface of the silicon-based negative electrode may undergo free radical polymerization under certain conditions (such as containing an initiator) to form a chemical bond. Under the action of the initiator, the fluoroalkyl monomer undergoes free radical polymerization, and the Si-OH on the silicon surface can serve as an active center to promote the growth of the polymer chain and form a strong bond with the silicon surface. In addition, the intermolecular van der Waals force between the fluoroalkyl monomer and the silicon surface will also enhance the adhesion of the polymer to the silicon surface.
[0051] The present invention selects a specific polymer monomer containing a fluoroalkyl group, which can make the hydroxyl group on the surface of the silicon-based negative electrode react with the functional group of the monomer in the polymer precursor as expected, and the functional group on the surface of the silicon-based material reacts with the functional group of the monomer in the polymer precursor solution, so that the silicon-based negative electrode and the polymer electrolyte are bonded together through intermolecular force and van der Waals force, thereby providing a strong binding force between the silicon-based negative electrode material and the polymer electrolyte. Therefore, when the volume of the silicon-based negative electrode expands during battery operation, the polymer electrolyte can exert a reaction force to effectively suppress its volume expansion, and the surface of the silicon-based negative electrode and the polymer electrolyte are bonded together, and the two form a good solid-solid contact, thereby effectively improving the solid-solid interface contact problem between the silicon-based negative electrode and the solid polymer, and providing sufficient channels for the transmission of ions and electrons; in addition, the polymer electrolyte can also form an effective polymer protective layer on the surface of the silicon-based negative electrode to prevent the corrosion of the silicon-based negative electrode by additives with low reduction stability or residual precursor monomers, thereby ensuring the stability of the battery system.
[0052] Optionally, the present invention further includes an intermediate membrane between the positive electrode and the silicon-based negative electrode, and the intermediate membrane is used as a supporting material for the in-situ solid electrolyte and as an isolation between the positive electrode and the silicon-based negative electrode.
[0053] Further optionally, the silicon-based negative electrode lithium battery also includes an inorganic solid electrolyte; for example, it may include: one or more of an oxide solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte. The inorganic solid electrolyte can be directly assembled in the lithium battery through an inorganic solid electrolyte diaphragm. When containing an inorganic solid electrolyte, the electrolyte of the solid-state battery of the present invention is an inorganic-organic composite electrolyte, which can give full play to the high mechanical properties of the inorganic electrolyte and the interfacial contact properties of the organic electrolyte, thereby ensuring good interfacial contact between the positive and negative electrode materials and the solid electrolyte. At the same time, the solid electrolyte has good mechanical properties and suppresses the volume expansion of the negative electrode.
[0054] The above describes the composition, basic properties and principles of the in-situ cured silicon-based negative electrode lithium battery of the present invention. Next, its preparation method is described.
[0055] The in-situ cured silicon-based negative electrode lithium battery of the present invention can be prepared by the following steps.
[0056] Step 1, prepare the positive electrode and the silicon-based negative electrode;
[0057] The positive electrode and silicon-based negative electrode of the present invention can be purchased from the market or prepared by yourself. The commercial lithium cobalt oxide positive electrode material used in the specific embodiment of the present invention was purchased from BASF Shanshan Battery Materials Co., Ltd., and the silicon material was purchased from Liyang Tianmu Xiandao Battery Materials Co., Ltd.
[0058] Among them, the material of the silicon-based negative electrode can specifically include silicon-based materials or composite materials of silicon and graphite; silicon-based materials include: one or more of pure silicon, silicon-carbon, and silicon-oxygen materials; in the composite material of silicon and graphite, the mass ratio of graphite to silicon is 0:100-90:10.
[0059] The surface of the silicon-based negative electrode material can be appropriately activated as needed, such as the aforementioned oxidizing acid treatment, alkaline washing or plasma treatment, to further increase the hydroxyl content of the silicon surface.
[0060] Step 2, preparing a polymer precursor solution;
[0061] Specifically, carbonate, acrylate and fluoroalkyl acrylate are mixed in a volume ratio of (1-3):1:(1-3) to obtain a polymerization monomer; in the preferred embodiment of the present invention, vinylene carbonate, ethylene glycol dimethacrylate and perfluorooctyl ethyl acrylate are mixed in proportion to obtain a polymerization monomer.
[0062] The polymerization monomer is added to the clarified solution containing the lithium salt according to the polymerization monomer: lithium salt mass ratio of 1:2-2:1, and after mixing evenly, an initiator accounting for 0.05%-1% by mass of the entire polymer precursor solution is added and mixed evenly to obtain a polymer precursor solution.
[0063] The lithium salt in the polymer precursor solution can be one or more of an inorganic lithium salt and an organic lithium salt, for example, one or more of LiPF6, LiBF4, LiClO4, LiAsF6, LiBOB, LiTFSI, LiDFOB, and LiFSI; the mass ratio of the polymer monomer to the lithium salt is 1:2-2:1, and can be any value within the above range, for example, 1:1, 1:1.5, 1:2, 1.5:1, and 2:1.
[0064] The clear solution containing the lithium salt includes the lithium salt and a solvent for the dissociable lithium salt; the solvent for the dissociable lithium salt includes a liquid organic solvent that can dissolve the lithium salt, and a solid organic matter that can form a homogeneous solution after being mixed with the lithium salt, such as one or more of succinonitrile, fluoroethylene carbonate, acetamide, methylacetamide, etc. The concentration of the lithium salt can be any value within the range of 0.1-10 mol / L.
[0065] An initiator is a substance that initiates polymerization of the monomers, including but not limited to free radical initiators such as azobisisobutyronitrile (AIBN) and 2-hydroxy-2-methyl-1-phenylpropanone. The mass percentage of the initiator in the polymer precursor solution is 0.05% to 1%. The mass percentage can be any value within this range, such as 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, or 1.0%.
[0066] Step 3, assembling a battery using a positive electrode and a silicon-based negative electrode, and injecting the polymer precursor solution into the battery;
[0067] The injection amount of the precursor solution is 1-10 g / Ah, which can be any value within the above range, such as 1 g / Ah, 2 g / Ah, 3 g / Ah, 4 g / Ah, 5 g / Ah, 6 g / Ah, 7 g / Ah, 8 g / Ah, 9 g / Ah, 10 g / Ah, but is not limited thereto.
[0068] When assembling a battery with a positive electrode and a silicon-based negative electrode, an intermediate membrane is also installed between the positive electrode and the silicon-based negative electrode. The intermediate membrane is used as a supporting material for the in-situ solid electrolyte and as an isolation between the positive electrode and the silicon-based negative electrode.
[0069] In addition, a diaphragm containing an inorganic solid electrolyte can also be used to construct an inorganic-organic composite solid electrolyte; the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte.
[0070] Step 4: Initiate polymerization of the polymer precursor solution by light and / or heat to obtain an in-situ cured silicon-based negative electrode lithium battery.
[0071] The precursor solution injected in the previous step can be cured by light and / or heat. The fluoroalkyl functional groups of the polymerizable monomers in the precursor solution interact with the hydroxyl functional groups in the silicon-based material, causing the fluoroalkyl polymer to accumulate on the surface of the silicon-based anode. After light and / or heat-induced curing, an in-situ cured silicon-based anode lithium battery is obtained.
[0072] The heat-induced heating temperature of the present invention is 50-100° C., and the heating time is 30 minutes to 48 hours. The heating temperature can be 50° C., 60° C., 70° C., 80° C., 90° C., or 100° C.; and the heating time can be 30 minutes, 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 24 hours, 30 hours, 48 hours, etc., but are not limited thereto.
[0073] The light initiation of the present invention can be performed by using an ultraviolet lamp with a certain wavelength to initiate in-situ curing. For example, an ultraviolet lamp with a wavelength of 365 nm is used for curing for 30 minutes to prepare an in-situ cured composite positive electrode plate.
[0074] The in-situ cured silicon-based negative electrode lithium battery of the present invention has high energy density, structural stability and excellent cycle performance. It can be applied to lithium batteries, lithium battery packs or lithium battery modules, and is widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields. It also has good application prospects in large-scale energy storage systems.
[0075] The assembly process of the in-situ cured silicon-based negative electrode lithium battery of the present invention is the same as the assembly process of the existing liquid lithium ion battery and can be used in common with existing equipment.
[0076] To make the objectives, technical solutions, and advantages of the present invention more apparent, the present invention will be further described in detail below with reference to the accompanying drawings. It is apparent that the embodiments described are only some, not all, of the present invention. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are intended to fall within the scope of protection of the present invention.
[0077] The reagents, positive electrode materials, negative electrode materials, polymer monomers, lithium salts, additives, and organic solvents used in the following examples and comparative examples were all commercially available or prepared according to the methods provided in the examples. Where specific experimental procedures or conditions are not specified in the examples, the procedures or conditions were followed according to conventional experimental procedures or conditions in the art.
[0078] Example 1
[0079] (1) Preparation of polymer precursor solution:
[0080] 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB) were weighed, mixed, and heated at 60°C for 2 h to obtain a clear solution;
[0081] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA), and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 300 μL: 100 μL: 100 μL and added to the clear solution, and 2 mg of the initiator azobisisobutyronitrile (AIBN) was added to obtain a mixture;
[0082] The mixture was stirred for 1 h to be uniformly mixed, thereby obtaining a polymer precursor solution.
[0083] (2) Assembling batteries:
[0084] 1) Assembly of silicon anode half-cell:
[0085] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 1.2 mAh / cm 2 .
[0086] The negative electrode was used as the working electrode, the lithium metal sheet as the counter electrode, and a glass fiber separator was used as the separator. A CR2032 button cell shell was used for assembly. The polymer precursor solution obtained in step (1) was injected into the cell at a volume of 100 μL. The assembled cell was then heated in a 60°C oven for 24 hours to cause polymerization of the precursor solution, resulting in an in-situ cured lithium battery.
[0087] 2) Assembly of silicon negative electrode full battery:
[0088] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 4 mAh / cm 2 .
[0089] Commercial lithium cobalt oxide positive electrode plate is used, with a plate surface capacity of 3.9mAh / cm 2 .
[0090] Assemble the negative and positive electrodes, along with a glass fiber separator, using a CR2032 button cell shell. Inject 100 μL of the polymer precursor solution obtained in step (1) into the battery. Heat the assembled battery in a 60°C oven for 24 hours to polymerize the precursor solution, resulting in an in-situ cured lithium battery.
[0091] Example 2
[0092] (1) Preparation of polymer precursor solution:
[0093] 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB) were weighed, mixed, and heated at 60°C for 2 h to obtain a clear solution;
[0094] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA), and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 100 μL: 100 μL: 300 μL and added to the clear solution, and 2 mg of the initiator azobisisobutyronitrile (AIBN) was added to obtain a mixture;
[0095] The mixture was stirred for 1 h to be uniformly mixed, thereby obtaining a precursor solution.
[0096] (2) Assembling batteries:
[0097] The specific method is the same as that of Example 1.
[0098] Example 3
[0099] (1) Preparation of polymer precursor solution:
[0100] The specific method is the same as that of Example 1.
[0101] (2) Assembling batteries:
[0102] 1) Assembly of silicon anode half-cell:
[0103] Silicon-carbon composite material (graphite: silicon = 90:10, mass ratio): conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, evenly coated on copper foil, and dried to obtain a negative electrode sheet with a surface capacity of 1.2 mAh / cm 2 .
[0104] The negative electrode was used as the working electrode, the lithium metal sheet as the counter electrode, and a glass fiber separator was used as the separator. A CR2032 button cell shell was used for assembly. The polymer precursor solution obtained in step (1) was injected into the cell at a volume of 100 μL. The assembled cell was then heated in a 60°C oven for 24 hours to cause polymerization of the precursor solution, resulting in an in-situ cured lithium battery.
[0105] 2) Assembly of silicon negative electrode full battery:
[0106] Silicon-carbon composite material (graphite: silicon = 90:10, mass ratio): conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, evenly coated on copper foil, and dried to obtain a negative electrode sheet with a surface capacity of 4 mAh / cm 2 .
[0107] Commercial lithium cobalt oxide positive electrode plate is used, with a plate surface capacity of 3.9mAh / cm 2 .
[0108] Assemble the negative electrode, positive electrode, and glass fiber separator in a CR2032 button cell shell. Inject 100 μL of the polymer precursor solution obtained in step (1) into the battery. Heat the assembled battery in a 60°C oven for 24 hours to polymerize the precursor solution, resulting in an in-situ cured lithium battery.
[0109] Example 4
[0110] (1) Preparation of polymer precursor solution:
[0111] The specific method is the same as that of Example 1.
[0112] (2) Assembling batteries:
[0113] 1) Assembly of silicon anode half-cell:
[0114] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 1.2 mAh / cm 2 .
[0115] The negative electrode was used as the working electrode, the lithium metal sheet as the counter electrode, and a polyethylene (PE) membrane coated with LATP solid electrolyte was used as the separator. A CR2032 button cell shell was used for assembly. The polymer precursor solution obtained in step (1) was injected into the cell at a volume of 100 μL. The assembled cell was then heated in a 60°C oven for 24 hours to cause polymerization of the precursor solution, resulting in an in-situ cured lithium battery.
[0116] 2) Assembly of silicon negative electrode full battery:
[0117] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 4 mAh / cm 2.
[0118] Commercial lithium cobalt oxide positive electrode plate is used, with a plate surface capacity of 3.9mAh / cm 2 .
[0119] The negative electrode and positive electrode sheets, along with a polyethylene (PE) separator coated with LATP solid electrolyte, were assembled in a CR2032 button cell shell. 100 μL of the polymer precursor solution obtained in step (1) was injected into the battery. The assembled battery was heated in a 60°C oven for 24 hours to polymerize the precursor solution, resulting in an in-situ cured lithium battery.
[0120] Example 5
[0121] (1) Preparation of polymer precursor solution:
[0122] 500 mg of succinonitrile (SN), 460 mg of lithium bis(fluorosulfonyl)imide (LiFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB) were weighed, mixed, and heated at 60 °C for 2 h to obtain a clear solution;
[0123] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA), and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 300 μL: 100 μL: 100 μL and added to the clear solution, and 2 mg of the initiator azobisisobutyronitrile (AIBN) was added to obtain a mixture;
[0124] The mixture was stirred for 1 h to be uniformly mixed, thereby obtaining a precursor solution.
[0125] (2) Assembling batteries:
[0126] The specific method is the same as that of Example 1.
[0127] Comparative Example 1
[0128] (1) Prepare electrolyte:
[0129] Lithium hexafluorophosphate (LiPF6) is dissolved in a composite solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1 to form an electrolyte, wherein the concentration of lithium hexafluorophosphate (Li PF6) is 1 mol / L, and fluoroethylene carbonate (FEC) accounting for 10% of the total volume of the electrolyte is added as an additive to the electrolyte.
[0130] (2) Assembling batteries:
[0131] 1) Assembly of silicon anode half-cell:
[0132] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 1.2 mAh / cm 2 .
[0133] The negative electrode was used as the working electrode, the metal lithium sheet was used as the counter electrode, and a glass fiber separator was used as the separator. A CR2032 button cell shell was used for button cell assembly. The electrolyte obtained in step (1) was injected into the battery at a volume of 100 μL.
[0134] 2) Assembly of silicon negative electrode full battery:
[0135] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 4 mAh / cm 2 .
[0136] Commercial lithium cobalt oxide positive electrode plate is used, with a plate surface capacity of 3.9mAh / cm 2 .
[0137] The negative electrode sheet, the positive electrode sheet, and the glass fiber separator were assembled using a CR2032 button battery shell, and the electrolyte obtained in step (1) was injected into the battery with an injection volume of 100uL.
[0138] Comparative Example 2
[0139] (1) Preparation of polymer precursor solution:
[0140] 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB) were weighed, mixed, and heated at 60°C for 2 h to obtain a clear solution;
[0141] The polymerization monomers vinylene carbonate (VC) and ethylene glycol dimethacrylate (PEGDA) were mixed at a ratio of 400 uL:100 uL and added to the clear solution, and 2 mg of the initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;
[0142] The mixture was stirred for 1 hour to be uniformly mixed, thereby obtaining a polymer precursor solution. The obtained polymer precursor solution does not contain a fluoroalkyl functional group.
[0143] (2) Assembling batteries:
[0144] The specific method is the same as that of Example 1.
[0145] Comparative Example 3
[0146] (1) Preparation of polymer precursor solution:
[0147] The specific method is the same as that of Example 1.
[0148] (2) Assembling batteries:
[0149] The silicon material is first pickled in hydrofluoric acid for 10 minutes, and the natural oxide layer SiO2 on the silicon surface is reactively etched by HF, thereby removing the oxide layer to reduce the surface hydroxyl groups and obtain a silicon material with less surface functional group content.
[0150] The treated silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, evenly coated on copper foil, and dried to obtain a negative electrode sheet with a surface capacity of 1.2 mAh / cm 2 .
[0151] The negative electrode was used as the working electrode, the lithium metal sheet as the counter electrode, and a glass fiber separator was used as the separator. A CR2032 button cell shell was used for assembly. The polymer precursor solution obtained in step (1) was injected into the cell at a volume of 100 μL. The assembled cell was then heated in a 60°C oven for 24 hours to cause polymerization of the precursor solution, resulting in an in-situ cured lithium battery.
[0152] 2) Assembly of silicon negative electrode full battery:
[0153] The silicon material is first pickled in hydrofluoric acid for 10 minutes, and the natural oxide layer SiO2 on the silicon surface is reactively etched by HF, thereby removing the oxide layer to reduce the surface hydroxyl groups and obtain a silicon material with less surface functional group content.
[0154] The treated silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, evenly coated on copper foil, and dried to obtain a negative electrode sheet with a surface capacity of 4 mAh / cm 2 .
[0155] Commercial lithium cobalt oxide positive electrode plate is used, with a plate surface capacity of 3.9mAh / cm 2 .
[0156] Assemble the negative and positive electrodes, along with a glass fiber separator, using a CR2032 button cell shell. Inject 100 μL of the polymer precursor solution obtained in step (1) into the battery. Heat the assembled battery in a 60°C oven for 24 hours to polymerize the precursor solution, resulting in an in-situ cured lithium battery.
[0157] Comparative Example 4
[0158] (1) Preparation of polymer precursor solution:
[0159] 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB) were weighed, mixed, and heated at 60°C for 2 h to obtain a clear solution;
[0160] The polymerization monomers vinylene carbonate (VC) and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 400 μL:100 μL and added to the clear solution, and 2 mg of the initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;
[0161] The mixture was stirred for 1 hour to be uniformly mixed, thereby obtaining a polymer precursor solution. The obtained polymer precursor solution does not contain a crosslinking agent.
[0162] (2) Assembling batteries:
[0163] The specific method is the same as that of Example 1.
[0164] The performance of the materials and batteries obtained in the above examples and comparative examples was characterized.
[0165] (1) Morphological characterization:
[0166] Figure 1 and Figure 2 They are respectively a scanning electron microscopy (SEM) image of the cross section of the material obtained after the precursor solution is polymerized in Example 1 and a scanning electron microscopy (SEM) image of the material surface. Figure 1 and Figure 2 As shown, the polymer electrolyte is densely covered on the glass fiber separator and penetrates into the gaps of the glass fiber separator, which indicates that the precursor solution can well infiltrate the separator and achieve uniform in situ polymerization, ensuring ion passage during the electrochemical cycle.
[0167] (2) Characterization of ingredients:
[0168] Figure 3 1 is a Fourier transform infrared spectroscopy (FTIR) analysis diagram of the monomer in the precursor solution of Example 1 and after polymerization. Figure 3The curves (a), (b), (c), (d) and (e) are the FTIR images of the electrolyte after in-situ polymerization, the silicon-based negative electrode after in-situ polymerization, the PEGDA monomer, the PFOEMA monomer and the VC monomer respectively. Figure 3 It can be seen that Figure 3 The 1642cm -1 The infrared absorption peak at corresponds to the stretching vibration of the C=C bond of PEGDA and HFOEMA. Figure 3 This characteristic peak does not exist in the curve (a) of , and the vibration peak disappears in the electrolyte after polymerization, indicating that the PEGDA and HFOEMA monomers are completely polymerized; Figure 3 3165cm in curve (e) -1 The infrared peak at comes from the stretching vibration of the =CH bond of vinylene carbonate (VC). Figure 3 The characteristic peak does not exist in curve (a). The disappearance of this vibration peak in the polymer electrolyte indicates that VC is completely polymerized. The peak corresponding to the double bond of the polymerized monomer in the polymer precursor solution disappears in the polymer solid electrolyte after polymerization, indicating that the polymerization reaction of the three monomers is complete. Figure 3 The characteristic peaks in curve (b) are different from those in curve (a). The characteristic peak intensity associated with curve (d) is higher, while the peak intensity associated with curve (e) is lower, indicating that the HFOEMA monomer is enriched on the silicon anode surface. The final polymer shows a gradient distribution from the silicon anode side to the separator side.
[0169] (3) Electrochemical performance test:
[0170] Electrochemical charge and discharge tests were performed on the batteries assembled from Examples 1-5 and Comparative Examples 1-4:
[0171] 1) 0.5C Cycling Performance Test at 30°C: The silicon anode half-cells used in the Examples and Comparative Examples were tested using a blue battery tester. The prepared half-cells were placed in a 30°C oven for charge and discharge testing over a voltage range of 5mV-1.5V. One cycle of activation was performed at 0.05C, followed by 100 cycles of charge and discharge at a constant current of 0.5C. Data for the initial discharge capacity, the 100th-cycle discharge capacity, and the 100th-cycle capacity retention were obtained, as shown in Table 1. Figure 4 This is a test chart of the 0.5C cycle performance of button batteries assembled in Examples 1-5 of the present invention and Comparative Examples 1-4 at 30°C.
[0172] Table 1 shows the test results of the in-situ polymerization and 30°C cycling performance of silicon anodes:
[0173]
[0174]
[0175] Examples 1-5 illustrate the present invention's in-situ cured silicon-based anode lithium batteries. The lithium battery in Comparative Example 1 utilizes an electrolyte supplemented with 10% FEC. The polymerized monomers in Comparative Example 2 contain no fluoroalkyl groups. The silicon anode in Comparative Example 3, due to prior hydrofluoric acid treatment, contains only very low levels of functional groups such as hydroxyl, carbonyl, and carboxyl. The polymerized monomers in Comparative Example 4 do not contain ethylene glycol dimethacrylate. The assembled batteries were subjected to cycling performance testing at 30°C.
[0176] The first discharge capacity of Example 1 at 0.05C is 2806.5mAh / g, the discharge capacity at 0.5C is 2196.5mAh / g, and the discharge capacity after 100 cycles at 0.5C is 2208.9mAh / g. The capacity retention rate is close to 100%, and no capacity decay occurs. Compared with Example 1, the volume ratio of the polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) in Example 2 is adjusted from 3:1:1 to 1:1:3. The first discharge capacity at 0.05C is 2249.6mAh / g, the discharge capacity at 0.5C is 1930.7mAh / g, and the discharge capacity after 100 cycles at 0.5C is 1861.7mAh / g. The capacity retention rate is close to 96.4%. Compared with Example 1, the polymer electrolyte in Example 4 also contains LATP solid electrolyte. Its initial discharge capacity at 0.05C was 2279.5 mAh / g, its discharge capacity at 0.5C was 1954.8 mAh / g, and its discharge capacity after 100 cycles at 0.5C was 1926.2 mAh / g, with a capacity retention rate of nearly 98.5%. Compared with Example 1, Example 5, which uses a different lithium salt in the polymer electrolyte, exhibited an initial discharge capacity of 2290.9 mAh / g at 0.05C, a discharge capacity of 1957.4 mAh / g at 0.5C, and a discharge capacity of 1911.3 mAh / g after 100 cycles at 0.5C, with a capacity retention rate of nearly 97.6%. It can be seen that the silicon-based negative electrode lithium batteries in Examples 1, 2, 4, and 5 all have high specific capacity and cycle stability.
[0177] Compared with Example 1, Example 3 selected a silicon-carbon negative electrode material mixed with graphite. Its first discharge specific capacity at 0.05C was 644.79 mAh / g, the discharge specific capacity at 0.5C was 554.88 mAh / g, and the discharge specific capacity after 100 cycles at 0.5C was 556.62 mAh / g. The capacity retention rate was 100%, that is, the capacity did not decay after 100 cycles. It can be seen that the silicon-based composite material obtained by mixing silicon material with graphite material still has a high specific capacity and exhibits excellent cycle stability.
[0178] Comparative Example 1 is a conventional liquid lithium-ion battery, which has an initial discharge capacity of 2080.9 mAh / g at 0.05C, a discharge capacity of 1885.8 mAh / g at 0.5C, a discharge capacity of 1613.8 mAh / g after 100 cycles at 0.5C, and a capacity retention rate of 85.6%. Compared with Comparative Example 1, Example 1 has an increased discharge capacity of 725.6 mAh / g at 0.05C, an increased discharge capacity of 310.7 mAh / g at 0.5C, an increased discharge capacity of 595.1 mAh / g after 100 cycles at 0.5C, and an increased capacity retention rate of 14.4% after 100 cycles. By comparison, it can be seen that compared with liquid lithium-ion batteries, the silicon negative electrode solid-state lithium battery obtained by the present invention using in-situ polymerization components has very good cycle stability at room temperature and still has excellent discharge capacity and capacity retention rate after long cycles.
[0179] The polyelectrolyte monomer in Comparative Example 2 does not contain fluoroalkyl functional groups, while the silicon negative electrode surface in Comparative Example 3 has only very low levels of hydroxyl, carbonyl, and carboxyl functional groups. The first discharge specific capacities of Comparative Examples 2 and 3 at 0.05C were 2504.6 mAh / g and 2179.8 mAh / g, respectively, and the discharge specific capacities at 0.5C were 1713.8 mAh / g and 1461.9 mAh / g, respectively. The battery assembled in Comparative Example 2 failed to cycle 100 cycles, while the capacity retention of the battery in Comparative Example 3 after 100 cycles at 0.5C was 43.1%. Compared to Comparative Examples 2 and 3, the discharge specific capacities of Example 1 at 0.05C increased by 301.9 mAh / g and 626.7 mAh / g, respectively, while the discharge specific capacities at 0.5C increased by 482.7 mAh / g and 734.6 mAh / g, respectively. After 100 cycles at 0.5C, the discharge specific capacity of Example 1 is 1578.1 mAh / g higher than that of Comparative Example 3. By comparison, it can be seen that the solid-state lithium batteries in Comparative Examples 2 and 3, the functional groups of the polymerized monomers and the functional groups on the silicon-based surface are different from those of the lithium-ion batteries of the present invention, and their discharge specific capacities are significantly lower than those of the present invention. The monomers in Comparative Example 2 do not contain fluoroalkyl functional groups. Although similar cycle stability was shown in the early stage, after 80 cycles, the discharge specific capacity plummeted and the battery failed. In Comparative Example 3, the silicon-based material in Example 1 was pickled to remove the surface functional groups, which showed poor cycle performance. Moreover, since the pickling caused structural damage to the material, the initial capacity was reduced. The cycle stability of Comparative Examples 2 and 3 is significantly lower than that of the present invention.
[0180] The electrolyte in Comparative Example 4 does not contain polymerized ethylene glycol dimethacrylate (PEGDA), that is, it does not contain a polymer component serving as a cross-linking agent. The resulting polymer solid electrolyte has poor mechanical properties, and obvious dendrite short circuiting occurs at the initial stage of the cycle, causing battery failure.
[0181] In summary, the silicon-based negative electrode battery of the present invention can maintain excellent cycle stability. The silicon-based negative electrode solid-state lithium battery obtained by in-situ polymerization of the polymer precursor monomer component with specific functional groups of the present invention and interaction with the silicon-based negative electrode rich in a large number of hydroxyl groups on the surface has very good cycle stability at room temperature and still has excellent discharge specific capacity and capacity retention rate after long cycles.
[0182] 2) High-temperature charge-discharge performance testing at 60°C: The silicon anode half-cells from Example 1 and Comparative Example 1 were tested using a blue-electric tester over a voltage range of 5mV-1.5V. One activation cycle was performed at 0.05C, followed by a constant current charge and discharge cycle at 0.5C. 60 cycles were performed to obtain the initial discharge capacity, the 60th-cycle discharge capacity, and the 60th-cycle capacity retention data, as shown in Table 2. Figure 5 This is a test chart of the high-temperature charge and discharge performance of button batteries assembled in Example 1 of the present invention and Comparative Example 1 at 60°C.
[0183] Table 2 shows the 60°C cycling performance test of silicon anode in-situ polymerization:
[0184]
[0185] Half-cells were assembled using the polymer precursor solution of Example 1 and the 10% FEC electrolyte obtained in Comparative Example 1. Cycling performance tests were conducted on both assembled half-cells at 60°C. The initial discharge capacity of Example 1 at 0.05C was 2445.36 mAh / g, the discharge capacity at 0.5C was 2166.91 mAh / g, and the discharge capacity after 60 cycles at 0.5C was 2012.11 mAh / g, with a capacity retention of 92.86%. For Comparative Example 1, the initial discharge capacity at 0.05C was 2467.41 mAh / g, the discharge capacity at 0.5C was 2180.96 mAh / g, and the discharge capacity after 60 cycles at 0.5C was 1692.26 mAh / g, with a capacity retention of 77.59%. It can be seen that when the cycle performance test is carried out at high temperature, the first discharge specific capacity at 0.05C and the first discharge specific capacity at 0.5C of Example 1 of the present invention are not much different from those of Comparative Example 1. Example 1 is slightly lower than Comparative Example 1, but the discharge specific capacity of Example 1 after 60 cycles at 0.5C is significantly higher than that of Comparative Example 1. The discharge specific capacity after 60 cycles at 0.5C is increased by about 319.85mAh / g, indicating that the silicon-based negative electrode battery of the present invention has excellent high-temperature capacity retention. By comparison, it can be seen that the silicon-based negative electrode solid-state battery obtained by the in-situ polymerization component of the present invention still has very good cycle stability at high temperature, and still has excellent discharge specific capacity and capacity retention after long cycles. The silicon-based solid-state battery obtained by in-situ polymerization of the present invention has excellent cycle stability under both normal temperature and high temperature conditions.
[0186] 3) Full-cell Charge and Discharge Performance Testing: The silicon anode and lithium cobalt oxide cathode button cells used in Example 1 and Comparative Example 1 were tested using a BlueDyne tester over a voltage range of 2.8 V to 4.45 V. The cells were first charged at 0.1 C to 4.45 V, then charged at a constant voltage to a rate of less than 0.025 C, and then discharged at a constant current of 0.1 C. The cycle was repeated 50 times to obtain the initial charge capacity, initial discharge capacity, initial coulombic efficiency, discharge capacity at the 50th cycle, and capacity retention at the 50th cycle, as shown in Table 3. Figure 6 This is a test diagram of the charge and discharge performance of the full battery assembled in Example 1 of the present invention and Comparative Example 1.
[0187] Table 3 shows the cycling performance test of silicon anode in-situ polymerization full battery at 30°C:
[0188]
[0189] Full cells were assembled using the polymer precursor solution of Example 1 and the 10% FEC electrolyte of Comparative Example 1, and the two assembled full cells were subjected to cycling performance tests at 30°C. The first charge capacity of Example 1 at 0.1C was 199.31 mAh / g, the discharge capacity was 174.56 mAh / g, the first coulombic efficiency was 87.59%, the discharge capacity after 50 cycles at 0.1C was 144.6 mAh / g, and the capacity retention rate was 82.8%. The first charge capacity of Comparative Example 1 at 0.1C was 203.59 mAh / g, the discharge capacity was 177.42 mAh / g, the first coulombic efficiency was 87.15%, the discharge capacity after 50 cycles at 0.1C was 115.8 mAh / g, and the capacity retention rate was 65.3%. It can be seen that when matched with high-voltage positive electrode lithium cobalt oxide to obtain a full battery, the charging specific capacity and discharge specific capacity of Example 1 at 0.1C are slightly inferior to those of Comparative Example 1, but the first coulombic efficiency is slightly higher than that of Comparative Example 1. The in-situ polymerization battery exhibits a higher first coulombic efficiency. Compared with Comparative Example 1, its first coulombic efficiency is increased from 87.15% to 87.59%. After the full batteries of Example 1 and Comparative Example 1 were cycled at 0.1C for 50 weeks, the discharge specific capacity and capacity retention rate of Example 1 were significantly better. The discharge specific capacity after 50 cycles at 0.1C was increased by about 28.8mAh / g compared with Comparative Example 1, an increase of about 24.9%, and the capacity retention rate was increased from 65.3% to 82.8%, an increase of about 17.5%. It can be seen that the full batteries of the present invention exhibit excellent electrochemical properties. By comparison, it can be seen that the silicon negative electrode solid-state lithium battery obtained by the in-situ polymerization component of the present invention has excellent first coulombic efficiency, cycle stability and capacity retention rate in the full battery test matching high-areal capacity and high-voltage lithium cobalt oxide, showing a wider electrochemical window, which can effectively match the high-voltage positive electrode to improve the energy density of the battery and show better electrochemical performance.
[0190] The in-situ solidified silicon-based negative electrode lithium battery provided by the embodiment of the present invention includes a positive electrode, a silicon-based negative electrode, and an in-situ solid electrolyte between the positive electrode and the silicon-based negative electrode. The surface of the silicon-based negative electrode is rich in a large number of hydroxyl groups. The in-situ solid electrolyte is obtained by in-situ polymerization of a polymer precursor solution. The polymerization monomer in the polymer precursor solution contains a fluoroalkyl functional group. The fluoroalkyl group has a strong interaction with the hydroxyl group on the surface of the silicon-based negative electrode, thereby achieving the aggregation of fluorine-containing polymers on the surface of the silicon-based negative electrode particles, and the polymer and the silicon-based negative electrode form a strong bond due to molecular forces, so that a stable and strong bond is formed between the in-situ solid electrolyte and the silicon-based negative electrode after in-situ polymerization. This stable and firmly bonded negative electrode-solid electrolyte interface can not only effectively suppress the volume expansion of the silicon-based negative electrode during the electrochemical cycle, but also effectively improve the interface performance and fully ensure the contact and transmission between ions. This stable anode-solid electrolyte interface not only effectively inhibits corrosion of the silicon-based anode by additives with low reduction stability or residual precursor monomers, but also more effectively matches the high-voltage positive electrode, thereby fully ensuring the high energy density and long-cycle stability of the lithium battery system. In addition, the fluoroalkyl group in the polymer monomer can significantly improve the thermal stability of the polymer electrolyte, thereby effectively ensuring the cycle stability of silicon-based anode batteries at high temperatures.
[0191] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An in-situ cured silicon-based negative electrode lithium battery, characterized in that: The in-situ cured silicon-based negative electrode lithium battery comprises: A positive electrode, a silicon-based negative electrode, and an in-situ solid electrolyte between the positive electrode and the silicon-based negative electrode, wherein the in-situ solid electrolyte is obtained by an in-situ polymerization reaction of a polymer precursor solution; The polymer precursor solution includes a polymer monomer, and the polymer monomer contains a fluoroalkyl group; the surface of the material of the silicon-based negative electrode is rich in hydroxyl groups; The silicon-based negative electrode and the in-situ solid electrolyte form a stable bond through at least two of hydrogen bonding, dipole-dipole interaction, free radical polymerization and van der Waals force; The fluorine concentration in the in-situ solid electrolyte is distributed in a gradient, gradually decreasing from the silicon-based negative electrode side to the positive electrode side.
2. The in-situ cured silicon-based negative electrode lithium battery according to claim 1, characterized in that: The polymerizable monomer is a composite system, comprising: carbonate, acrylate and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3), preferably vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) in a volume ratio of (1-3):1:(1-3).
3. The in-situ cured silicon-based negative electrode lithium battery according to claim 1, characterized in that: The polymer precursor solution further includes lithium salt, and the mass ratio of the polymer monomer to the lithium salt is 1:2-2:1; and / or, The polymer precursor solution also includes an initiator, and the mass percentage of the initiator in the polymer precursor solution is 0.05%-1%.
4. The in-situ cured silicon-based negative electrode lithium battery according to claim 1, characterized in that: The material of the silicon-based negative electrode is a silicon-based material or a composite material of silicon and carbon; The silicon-based material includes: one or more of pure silicon, silicon-carbon compounds, lithium-silicon compounds, lithium-silicon-carbon compounds, and silicon-oxygen compound materials; The composite material of silicon and carbon is preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:
10.
5. The in-situ cured silicon-based negative electrode lithium battery according to claim 1, characterized in that: An intermediate film is also included between the positive electrode and the silicon-based negative electrode, and the intermediate film is used as a supporting material for the in-situ solid electrolyte and as an isolation between the positive electrode and the silicon-based negative electrode.
6. The in-situ cured silicon-based negative electrode lithium battery according to claim 1, characterized in that: The silicon-based negative electrode lithium battery also includes an inorganic solid electrolyte; the inorganic solid electrolyte includes: one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.
7. A method for preparing an in-situ cured silicon-based negative electrode lithium battery according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Prepare positive electrode and silicon-based negative electrode; preparing a polymer precursor solution; Assembling a battery with the positive electrode and the silicon-based negative electrode, and injecting the polymer precursor solution into the battery; the injection amount of the precursor solution is 1-10g / Ah; The polymer precursor solution is polymerized by initiating light and / or heat to obtain the in-situ cured silicon-based negative electrode lithium battery.
8. The preparation method according to claim 7, characterized in that: The preparation of the polymer precursor solution specifically comprises: Mixing carbonate, acrylate and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3), preferably mixing vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) in a volume ratio of (1-3):1:(1-3) to obtain a polymerized monomer; Adding the polymerizable monomer to the clarified solution containing the lithium salt in a mass ratio of 1:2-2:1 of the polymerizable monomer:lithium salt, and adding an initiator accounting for 0.05%-1% of the mass percentage of the whole polymer precursor solution after mixing evenly, and mixing evenly to obtain a polymer precursor solution; The clear solution containing lithium salt comprises: lithium salt and a solvent capable of dissociating lithium salt; the solvent comprises one or more of a liquid organic solvent capable of dissolving lithium salt and a solid organic matter capable of coordinating with lithium salt to form a homogeneous solution; and the lithium salt concentration of the solution is 0.1-10 mol / L.
9. The preparation method according to claim 7, characterized in that: The material of the silicon-based negative electrode is a silicon-based material or a composite material of silicon and carbon; The silicon-based material includes: one or more of pure silicon, silicon-carbon compounds, lithium-silicon compounds, lithium-silicon-carbon compounds, and silicon-oxygen compound materials; The composite material of silicon and carbon is preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:
10.
10. The preparation method according to claim 7, characterized in that: When assembling a battery using the positive electrode and the silicon-based negative electrode, an intermediate membrane is also installed between the positive electrode and the silicon-based negative electrode. The intermediate membrane is used as a supporting material for the in-situ solid electrolyte and as an isolation between the positive electrode and the silicon-based negative electrode.
Citation Information
Cited By
Secondary battery and preparation method thereof, energy storage system and electric equipment
CN121076265A